Hubungan Psychological Capital Dengan Kepuasan Kerja Pada Anggota Polri Yang Sedang Mengikuti Pendidikan Di Perguruan Tinggi Ilmu Kepolisian (PTIK) - Hedissa, Aldia Thirzady; Sukhirman, Iman; Supandi, Andi (Jurnal Psikologi: PITUTUR, 2012)
This thesis discusses the relationship between Job Satisfaction PsyCap with  the  police  officers  who  are  following  in PTIK  education,  as  the candidates head of police in the future. The study is a quantitative research also aims to see the picture PsyCap and job satisfaction in participants. The results of the study indicate that the picture PsyCap and job satisfaction in police officers who were to attend a PTIK are at moderate levels; there is arelationship  between  job  satisfaction  PsyCap;  and  PsyCap  only  twodimensions, namely resiliency and optimism related to job satisfaction.